2003
DOI: 10.1086/378853
|View full text |Cite
|
Sign up to set email alerts
|

A Long Look at NGC 3783 with theXMM‐NewtonReflection Grating Spectrometer

Abstract: A long 280 ks observation of the Seyfert 1 galaxy NGC 3783 with XMM-Newton is reported. We focus on the oxygen line complex between 17 and 24 Å as measured with the Reflection Grating Spectrometer. Accurate absorption column densities and emission-line fluxes are obtained. We explore several options for the geometry and physical form of the emitting and absorbing gas. The lack of change in ionization in the absorber despite an increase in continuum flux during the observation restricts the high-ionization (O-K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(186 citation statements)
references
References 35 publications
14
172
0
Order By: Relevance
“…The strongest line visible in a typical Seyfert 1 high-resolution X-ray spectrum is the O vii forbidden emission line, although other lines are also detected depending on the quality of the spectrum (among others Ne ix f and C v f). No significant blueshift is detected in the emission lines of NGC 5548 (Kaastra et al 2002), while NGC 3783 shows evidence of redshifted emission lines, which could be an indication of a P-Cygni like wind (Kaspi et al 2002;Behar et al 2003).…”
Section: Introductionmentioning
confidence: 85%
“…The strongest line visible in a typical Seyfert 1 high-resolution X-ray spectrum is the O vii forbidden emission line, although other lines are also detected depending on the quality of the spectrum (among others Ne ix f and C v f). No significant blueshift is detected in the emission lines of NGC 5548 (Kaastra et al 2002), while NGC 3783 shows evidence of redshifted emission lines, which could be an indication of a P-Cygni like wind (Kaspi et al 2002;Behar et al 2003).…”
Section: Introductionmentioning
confidence: 85%
“…Such SMW jets can inflate fat bubbles (Sternberg et al 2007), and through that transfer energy to the ICM (or ISM) and make the JFM efficient in galactic (e.g., Ciotti et al 2010;Choi et al 2015) and cluster (e.g., Gilkis & Soker 2012) scales. Wide-angle sub-relativistic outflows are revealed by X-ray observation as well (e.g., Behar et al 2003). Chartas et al (2016) for example, find the outflow from the AGN HS 0810+2554 to have a covering factor of > 0.6, and to carry about ten times more energy than that carried by radiation from the AGN.…”
Section: The Jetsmentioning
confidence: 98%
“…Previous studies have found a WA in NGC 3783 (Kaspi et al 2002;Blustin et al 2002;Behar et al 2003;Scott et al 2014). We utilised all archival data from XMM- Newton (2000 and2001) and Chandra HETGS (2000, 2001, and 2013) to produce a set of time-averaged spectra.…”
Section: Modelling Of the Obscuring Wind In Ngc 3783mentioning
confidence: 99%